Changes in the Surface Chemistry and Adsorptive Properties of Active Carbon Previously Oxidized and Heat-Treated at Various Temperatures. III. Studies of the Adsorption of Organic Solutes from Aqueous Solutions - A. Derylo-Marczewska; A. Swiatkowski; H. Grajek; S. Biniak; Z. Witkiewicz (Adsorption Science & Technology)
The dependence between the surface chemistry characteristics of thermally modified active carbon samples with previously oxidized surfaces and their ability to adsorb organic solutes from aqueous solutions was investigated. The characteristics of the surface functional groups and the porous structure of the samples obtained were estimated using various experimental methods. The adsorption isotherms of nitrobenzene and 4-nitrophenol from dilute aqueous solutions onto all the carbon samples obtained were measured. The experimental systems were analyzed in terms of the theory of adsorption onto energetically heterogeneous solids. The relationships between the optimized isotherm parameters, i.e. equilibrium constants and heterogeneity parameters, and the characteristics of the active carbons were discussed.